2012
DOI: 10.1097/mph.0b013e3182288249
|View full text |Cite
|
Sign up to set email alerts
|

A Novel mtDNA Large-Scale Mutation Clinically Exclusively Presenting With Refractory Anemia

Abstract: We report a rare case of juvenile cobalamin deficiency who presented at the age of seventeen years. He was underweight and had skin changes, normocytic anemia and autonomic dysfunction which lead to adynamic ileus and acute post-renal failure. The expected macrocytosis was masked by an underlying alpha thalassemia trait. The patient had an excellent response to parenteral cobalamin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This finding is consistent with other reports, where anaemia was also more frequent in MIDs than abnormalities in thrombocyte or leucocyte count (either as the sole, dominant or collateral feature of the phenotype) (Table VIII). (17,21) Although anaemia as a sole manifestation of MID was not seen in the present study, it has been previously reported in a patient carrying a large-scale mtDNA deletion (encompassing the genes ATPase6, COX-III, ND3, ND4, ND5, ND6 and cytb). (21) In another case, a mutation in the nDNA-located gene, SLC25A38, which encodes a carrier of the inner mitochondrial membrane, resulted in isolated non-syndromic microcytic, hypochromic and sideroblastic anaemia (autosomal recessive pyridoxinerefractory sideroblastic anaemia).…”
Section: Syndromicmentioning
confidence: 46%
See 2 more Smart Citations
“…This finding is consistent with other reports, where anaemia was also more frequent in MIDs than abnormalities in thrombocyte or leucocyte count (either as the sole, dominant or collateral feature of the phenotype) (Table VIII). (17,21) Although anaemia as a sole manifestation of MID was not seen in the present study, it has been previously reported in a patient carrying a large-scale mtDNA deletion (encompassing the genes ATPase6, COX-III, ND3, ND4, ND5, ND6 and cytb). (21) In another case, a mutation in the nDNA-located gene, SLC25A38, which encodes a carrier of the inner mitochondrial membrane, resulted in isolated non-syndromic microcytic, hypochromic and sideroblastic anaemia (autosomal recessive pyridoxinerefractory sideroblastic anaemia).…”
Section: Syndromicmentioning
confidence: 46%
“…(17,21) Although anaemia as a sole manifestation of MID was not seen in the present study, it has been previously reported in a patient carrying a large-scale mtDNA deletion (encompassing the genes ATPase6, COX-III, ND3, ND4, ND5, ND6 and cytb). (21) In another case, a mutation in the nDNA-located gene, SLC25A38, which encodes a carrier of the inner mitochondrial membrane, resulted in isolated non-syndromic microcytic, hypochromic and sideroblastic anaemia (autosomal recessive pyridoxinerefractory sideroblastic anaemia). (17) Anaemia as the sole feature of the phenotype is also characteristic of XLSA.…”
Section: Syndromicmentioning
confidence: 46%
See 1 more Smart Citation
“…No strict correlations have been observed between heteroplasmy in blood cells and the severity of hematopoietic features. Furthermore, no obvious genotype-phenotype correlation has been identified regarding the appearance of hematological manifestations in PS and the mtDNA deletion (18). The different phenotypic expression of the same mtDNA defects may be associated with nuclear modifier genes, polymorphisms and environmental factors (19).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of CPEO patients present homoplasmic large-scale deletions in mitochondrial DNA (mtDNA) [4]. Mitochondrial disease-associated FSGS has mainly been reported in patients with mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) [5], another type of mitochondrial disease caused by heteroplasmic point mutations in mtDNA, mainly m.3243A>G transitions.…”
Section: Introductionmentioning
confidence: 99%